The first need: hunger in Jan Němec's Diamonds of the Night. Issue 2 (3rd May 2016) - O'Key, Dominic
ABSTRACT: This article analyses the semiotic grammar of food in Jan Němec's surreal film Démanty noci / Diamonds of the Night (1964). After first locating Diamonds within the Czechoslovak New Wave and a tradition of Holocaust literature and cinema, I explore the film's representation of hunger and thirst. My analysis synthesises the film with Primo Levi's evocative meditation on the victims of the Holocaust, arguing that Němec's protagonists become a form of 'living hunger', and enter into a 'condition of pure survival'. The film thus comments on the totalising Nazi mission and its attempt to desubjectify its victims by laying claim to their bodies.